ANALISIS KINERJA PORTOFOLIO SAHAM DENGAN MENGGUNAKAN METODE INDEKS SHARPE, TREYNOR DAN JENSEN PADA KELOMPOK SAHAM INDEKS SRI-KEHATI DI BURSA EFEK INDONESIA - Dwi Susilowati; Juwari Juwari; Chinta Noviadinda (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2020)
Stock Portfolio Performance Analysis Using the Sharpe, Treynor, and Jensen Index Methods in the SRI-KEHATI Index Stock Group on the Indonesia Stock Exchange. The purpose of this study is to determine the performance of optimal stock portfolios in the SRI-KEHATI index stock group on the Indonesia Stock Exchange in the period November 2018-October 2019. The method of data analysis uses a single index model to form an optimal portfolio and use the Sharpe, Treynor, and Jensen index methods to assess the performance of a stock portfolio. Based on the analysis of optimal portfolio formation shows that on the first semester there were 16 stocks that entered the optimal portfolio out of a total of 24 stocks as sample with an expected return of 6.00% and a risk of 0.82%. In the second semester there were only 5 stocks that entered the optimal portfolio out of a total of 24 stocks as sample with an expected return of 1.50% and a risk of 0.15%. Furthermore, the results of the analysis of stock portfolio performance assessment shows that of the three portfolio performance assessment index methods, the index method that provides the best performance in the SRI-KEHATI index on the Indonesia Stock Exchange is the Sharpe index method, which is on the first semester portfolio with an index value of 0.60567. The higher Sharpe index value, the better performance of stock portfolio.